ANALISIS KOLEKTOR SEDERHANA BERGELOMBANG DENGAN PENAMBAHAN REFLEKTOR TERHADAP KINERJA SOLAR WATER HEATER - Sutrisno, Sutrisno; Mustafa, Mustafa (JURNAL AGRI-TEK, 2014)
Utilization of solar energy has grown rapidly. In this regard has been much research done to obtain maximum results and effective. In this study developed with the addition feflektor corrugated collector. Serves as a heat reflector enhancer on the plate with reflected light, it is intended to add to the heat received by the plate. This research method is done by experiments using two (2) pieces of corrugated plates and PVC plates with the addition of a glass reflector taste, so it can produce more heat. Reflector serves reflect sunlight towards the plate absorber so that more effective heat absorption and maximum. The study concluded that the addition of reflectors make better absorption.Keyword: solar water heater, PVC plate, reflector.